FULL STACK WEB DEVELOPMENT INTERFACE MANGMENT SYSTEM FOR MEGA PROJECTS - Khaled A. Hamdy; Amin Saleh; Abdallah Hosny (Proceedings on Engineering Sciences)
This paper aims to enhance communication, collaboration and coordination interface points among stakeholders and various disciplines participation in the project directly and indirectly by defining the roles and responsibilities of all project parties, as well as monitoring issues and problems among the project stakeholders. This approach produces developed web system illustrates the architecture and implementation of a web-based IMS developed in C# .NET 8 MVC, leveraging Entity Framework for data management. The system allows for user registration, project management, and the creation of interface points critical for project coordination. This system will detail the role definitions, user workflows, and essential database schema. then delves into the specific requirements and meticulous design of an IMS tailored to address the myriad challenges faced in construction projects today. The system is designed to delineate user roles with precision, particularly focusing on project members such as coordinators appointed by contractors. These roles will be defined with explicit responsibilities and permissions to ensure clarity and efficiency in project execution. the proposed IMS is designed to foster enhanced collaboration among the various participants involved in a project, allowing stakeholders to manage interface points with heightened efficiency. Moreover, the IMS will guarantee that all critical data pertaining to project interface points are correct.